Validation of the energy consumption model for a quadrotor using Monte-Carlo simulation - Robert Głębocki; Marcin Żugaj; Mariusz Jacewicz (Archive of Mechanical Engineering, 2022)
Unmanned, battery-powered quadrotors have a limited onboard energy resources. However, flight duration might be increased by reasonable energy expenditure. A reliable mathematical model of the drone is required to plan the optimum energy management during the mission. In this paper, the theoretical energy consumption model was proposed. A small, low-cost DJI MAVIC 2 Pro quadrotor was used as a test platform. Model parameters were obtained experimentally in laboratory conditions. Next, the model was implemented in MATLAB/Simulink and then validated using the data collected during real flight trials in outdoor conditions. Finally, the Monte-Carlo simulation was used to evaluate the model reliability in the presence of modeling uncertainties. It was obtained that the parameter uncertainties could affect the amount of total consumed energy by less than 8% of the nominal value. The presented model of energy consumption might be practically used to predict energy expenditure, battery state of charge, and voltage in a typical mission of a drone.